Temperature measurement within myocardium during in vitro RF catheter ablation - Cao, Hong; Vorperian, Vicken R.; Tsai, Jang Zern; Tungjitkusolmun, Supan; Je Woo, Eung; Webster, John G. (My University, 2000)
While most commercial ablation units and research systems can provide catheter tip temperature during ablation, they do not provide information about the temperature change inside the myocardium, which determines the lesion size. We present the details of a flow simulation and temperature measurement system, which allows the monitoring of the temperature change inside the myocardium during in vitro radio frequency (RF) cardiac catheter ablation at different blood flow rates to which the catheter site may be exposed. We set up a circulation system that simulated different blood flow rates of 0 to 5 L/min at 37°C. We continuously measured the temperature at the catheter tip using the built-in thermistor and inside the myocardium using a three-thermocouple probe. The system provides a means for further study of the temperature inside myocardium during RF catheter ablation under different flow conditions and at different penetration depths.
Keywords: Electrical interference; Radiofrequency cardiac ablation; Temperature measurement; Thermistor; Thermocouple